Material-flow behavior during friction-stir welding of 6082-T6 aluminum alloy. Issue 1 (October 2016) - Huang, Yongxian; Wang, Yaobin; Wan, Long; Liu, Haoshu; Shen, Junjun; Santos, Jorge; Zhou, Li; Feng, Jicai
Abstract Material-flow behavior during friction-stir welding of 6082-T6 aluminum alloy has been visualized by marker insert technique. Four stacked layers were evolved in welding nugget zone (WNZ) in the transverse section. The material-flow behavior in vertical direction was detected by observing the distribution of Cu foil fragments and Al-Cu intermetallic compounds. The downward and upward flows encounter each other at the advancing side in the material depositing process, changing the morphology of WNZ. A conceptual balanced-flow model and a plastic material-flow model were used to describe the material-flow behavior, and the origin of the downward material flow in the advancing side was discussed. The excess-material flow derived by the welding tool due to the existence of the tilt angle is crucial to the weld formation.